An overview of different strategies involved in an efficient control of emerging contaminants: Promising enzymes and the related reaction process. Issue 5 (October 2022) - Ouyang, Binbin; Xu, Wei; Zhang, Wenli; Guang, Cuie; Mu, Wanmeng
Abstract: Emerging contaminants (ECs) are primarily composed of the synthetic organic chemicals, arising from industry emission, medicinal, husbandry, and domestic waste. ECs such as polycyclic aromatic hydrocarbons (PAHs), perfluorinated compounds (PFCs), and pharmaceutical and personal care products (PPCPs) not only make a serious threat on the environment conditions but also human health. A comprehensive review about ECs including the occurrence and ecotoxicity, as well as the controlling strategies was made. Firstly, the idea of ECs "block" was introduced to connect different ECs during the supply of feed and food chain. The existence of ECs in different contaminant blocks would eventually affect human health. Secondly, the conventional strategies including physical, chemical, and biological methods against ECs were presented such as the removal of PPCPs and PAHs. Notably, conventional strategies like filtration, adsorption, and sedimentation could hardly eliminate the parent compound of ECs. Last but not least, the biological strategies employed by the oxidoreductases (ORs) group like lignin peroxidase, manganese peroxidase, laccase, and horseradish peroxidase were also evaluated for ECs elimination. Although the elimination of pharmaceuticals by the lignin peroxidase and laccase in lab-scale are gratifying, the removal of other ECs like PAHs, and PFCs are still insufficient by the ORs family. All in all, a combination of conventional strategies with enzymatic-based catalysis would greatly integrate the advantages and allow a promising, efficient, and eco-friendly controllable solution to ECs decontamination. Graphical Abstract: ga1 Highlights: The occurrence, toxicity and control strategy about ECs were presented. Chemical, physical and biological solutions were discussed together. Several promising oxidoreductases against different ECs were highlighted. Characteristics, structures and application of oxidoreductase are shown.